PEMBUDAYAAN DEMOKRASI DI PESANTREN DALAM MENGEMBANGKAN CIVIC DISPOSITION SANTRI - Supangat Supangat; Muhammad Halimi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2017)
Abstract: This article is motivated by issues attitude and character of citizenship among the younger generation which is very alarming. The understanding of democracy that one result of excessive democratic freedoms. Disorientation attitude and character citizenship (civic disposition) experienced by almost all elements of the nation thus eliminating the identity of the nation and much of the value-milai democracy. Pesantren Daarut Tauhid as modern schools also provide planting of democratic values among his students. The data were taken with the study documentation, observations, interviews, and the active participation of researchers in the field. The results of this study found: democracy education should be introduced in educational institutions schools, for boarding institutions are educational institutions which make the process of developing the potential of learners (students). Through the process of democratic education will produce a democratic man.For students develop civic disposition, pendidikkan process conducted in schools in various ways; 1) exemplary; 2) exercise and habituation; 3) educate through ibrah (taking lessons); 4) educate through mauidzah (advice); 5) educate through discipline; and 6) educate targib wa tahzid (inducements and threats) Abstrak: Artikel ini dilatarbelakangi oleh persoalan sikap dan watak kewarganegaran di kalangan generasi muda yang sangat memprihatinkan. Pemahaman terhadap demokrasi yang salah mengakibatkan kebebasan berdemokrasi yang kebablasan. Disorientasi sikap dan watak kewarganegaraan (civic disposition) hampir dialami oleh seluruh elemen bangsa sehingga menghilangkan jati diri anak bangsa dan jauh dari nilai-milai demokrasi. Pesantren Daarut Tauhid sebagai pesantren modern juga memberikan penanaman nilai-nilai demokrasi dikalangan para santrinya. Data dalam penelitian ini diambil dengan studi dokumentasi, observasi, wawancara, dan partisipasi aktif peneliti dilapangan. Hasil dari penelitian ini ditemukan: Pendidikan demokrasi hendaknya dikenalkan di lembaga pendidikan pesantren, karena lembaga pesantren merupakan lembaga pendidikan yang melakukan proses mengembangkan potensi peserta didik (santri). Melalui proses pendidikan demokrasi akan menghasilkan manusia yang demokratis.Untuk  mengembangkan civic disposition santri, proses pendidikkan yang dilakukan di pesantren dengan berbagai cara yaitu; 1) keteladanan; 2) latihan dan pembiasaan; 3) mendidik melalui ibrah (mengambil pelajaran); 4) mendidik melalui mauidzah (nasehat); 5) mendidik melalui disiplin; dan 6) mendidik targib wa tahzid (bujukan dan ancaman) DOI : http://dx.doi.org/10.17977/um019v2i12017p075